Pravidlá na úpravu regulárnych výrazov : pomocou nich možno zjednodušiť regulárny výraz

          P + Q = Q + P
          P + (Q + R) = (P + Q) + R
          P . (Q . R) = (P . Q) . R
          P . Q + P . R = P . (Q + R)
          P . R + Q . R = (P + Q) . R
          (P + Q)* = (P* + Q*)* = (P* . Q*)*
          (P*)* = P*
          P . = . P =
          P* . P* = P*
          P . P* = P* . P
          P* + P = P*
          P* = + P . P*
           . P = P . = P
          P + = P
          P + P = P
          * =
          * =